Analisis Komperatif Pengaruh Laba Neto dan Arus Kas Masuk terhadap Dividen Tunai pada Perusahaan Manufaktur Barang Konsumsi Di BEI - Gen Norman Thomas (Bina Nusantara University, 2014)
This study aims to comparatively analyze the relationship and effect of net income to cash dividend and the the relationship and effect of operating cashinflows to cash dividend on consumer goods manufacturing companies listed The Indonesia Stock Exchange. The method used is a quantitative method to test the hypothesis, and the hypothesis of the test is carried out a comparative analysis between net income and operating cashinflows to cash dividends. This study aims to analyze comparatively relationship and influence of net income andrelationship and influence of cash inflows to cash dividend in the consumer goods manufacturing companies listed in Indonesia Stock Exchange. The results of this study indicate that relationship and influence of net income have effect lower than relationship and influence of cashinflow to cash dividend, although the relationship and influence of the two independent variables to the cash dividend are both very strong and high.